Hubungan Antara Pemanfaatan Internet Terhadap Hasil Belajar Geografi Siswa SMA Negeri 1 Negeri Besar - Maisaroh Maisaroh; Sumadi Sumadi; Dedy Miswar (JPG (Jurnal Penelitian Geografi), 2019)
The purpose of this research was to find out the use of the internet towards geography learning result of the students at SMAN 1 Negeri Besar. Ex post facto design  was used of in research. The population of this research was students at SMAN 1 Negeri Besar and the sample of this research was 79 students. Random sampling was used as technique in this research. Questionnare and observation sheet were used as instruments. This research used correlation product moment to analyze data. The result showed that there were three point of this research. First, there was a correlation between students’result in learning geography towards the use of the interenet (0,236). Second, there was not enough evidence to indicate a positive correlation and there was no significant improvement of students’ result in learning geography by using the ease of internet information (0,071). Third, there was not enough evidence to confirm a positive and significant relationship between internet access and result of students’ geography learning (0,064).Penelitian ini bertujuan mengetahui hubungan pemanfaatan internet terhadap hasil belajar geografi siswa SMA Negeri 1 Negeri Besar. Metode penelitian yang digunakan ex post facto dengan populasi seluruh siswa dan sampel yang digunakan sebanyak 79 siswa menggunakan teknik Proforsional Random Sampling. Pengumpulan data yang digunakan kuisioner dan observasi. Analisis data yang digunakan rumus Korelasi Product Moment. Hasil menunjukkan: 1) Terdapat hubungan intensitas penggunaan internet terhadap hasil belajar geografi siswa ditunjukkan dari nilai (0,236). 2) Tidak terdapat bukti cukup untuk menyatakan ada hubungan positif dan signifikan kemudahan informasi internet terhadap hasil belajar geografi siswa ditunjukkan dari nilai (0,071). 3) Tidak terdapat bukti cukup untuk menyatakan ada hubungan positif dan signifikan kerelevansian akses internet terhadap hasil belajar geografi siswa ditunjukkan dari nilai (0,064).Kata kunci :geografi, hasil belajar, pemanfaatan internet